Síntese verde de nanopartículas de prata e ouro utilizando extrato de Monteverdia ilicifolia e modificação de eletrodos a base de carbono para detecção de cloridrato de trazodona e succinato de desvenlafaxina - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2025)
In this work, four modified electrodes were developed: two carbon paste electrodes (CPE) and two ceramic carbon electrodes (CCE), each functionalized with gold (AuNPs) or silver nanoparticles (AgNPs), synthesized via ultrasound-assisted methods using crude ethanolic extract from Monteverdia ilicifolia (MI) leaves as both reducing and stabilizing agent. UV-Vis spectroscopy confirmed nanoparticle formation with characteristic bands at 520 nm for AuNPs- MI and 410 nm for AgNPs-MI. Transmission electron microscopy revealed average diameters of 10.62 ± 2.1 nm for AuNPs-MI and 12.28 ± 3.7 nm for AgNPs-MI. Antioxidant activity assays using ABTS•+ and DPPH• radicals showed significant activity for the MI extract, with IC50 values of 12.86 and 28.58 μg mL−1, respectively. The nanoparticles exhibited lower antioxidant activity, indicating the consumption of phenolic compounds during synthesis. Electrochemical characterization using cyclic voltammetry and electrochemical impedance spectroscopy with the Fe(CN)63−/4− redox probe demonstrated that the nanomaterials enhanced peak currents and reduced charge transfer resistance. The electrodes were first applied to the detection of trazodone hydrochloride (TRZ), which showed two oxidation processes at 0.85 and 1.12 V in pH 7. Desvenlafaxine (DVX) also exhibited oxidation, with a single process at 0.59 V in pH 10, both systems being pH-dependent. Using differential pulse voltammetry (DPV), analytical curves were constructed for TRZ with the following results: CCE/AuNPs-MI (linear range: 10.1–48.0 μmol L−1, LOD: 5.9 μmol L−1, LOQ: 19.8 μmol L−1), CCE/AgNPs-MI (7.8–50.0 μmol L−1, LOD: 3.82 μmol L−1, LOQ: 12.7 μmol L−1), CPE/AuNPs-MI (45.0–78.0 μmol L−1, LOD: 5.07 μmol L−1, LOQ: 16.9 μmol L−1), and CPE/AgNPs-MI (23.0–55.0 μmol L−1, LOD: 4.09 μmol L−1, LOQ: 13.6 μmol L−1). For DVX, the results were: CCE/AuNPs-MI (150–600 μmol L−1, LOD: 34.0 μmol L−1, LOQ: 113 μmol L−1), CCE/AgNPs-MI (100–600 μmol L−1, LOD: 17.0 μmol L−1, LOQ: 56.0 μmol L−1), CPE/AuNPs-MI (50–600 μmol L−1, LOD: 8.14 μmol L−1, LOQ: 27.0 μmol L−1), and CPE/AgNPs-MI (50–500 μmol L−1, LOD: 8.91 μmol L−1, LOQ: 30.0 μmol L−1). The electrodes were also applied to the analysis of pharmaceutical samples, showing for TRZ precision and recovery values of 88.06 and 103.76% (CCE/AuNPs- MI), 96.75 and 99.67% (CCE/AgNPs-MI), 96.81 and 103.94% (CPE/AuNPs-MI), and 94.06 and 106.21% (CPE/AgNPs-MI). For DVX, the results were 98.99 and 100.79% (CCE/AuNPs- MI), 99.98 and 94.82% (CCE/AgNPs-MI), 99.55 and 97.60% (CPE/AuNPs-MI), and 99.94 and 97.06% (CPE/AgNPs-MI).
Keywords: eletrodo de pasta de carbono; eletrodo de carbono cerâmico; nanopartículas de ouro; nanopartículas de prata; síntese verde; voltametria de pulso diferencial; cloridrato de trazodona; succinato de desvenlafaxina; carbon paste electrode; carbon-ceramic electrode; gold nanoparticles; silver nanoparticles; green synthesis; differential pulse voltammetry; trazodone hydrochloride; desvenlafaxine succinate; Química